Public Policy Instruments Selected in Policy Implementation Prostitution Prevention and Revocation in Surabaya City - Ati, Nurul Umi; Zauhar, Soesilo; Sarwono, Sarwono; Indah Mindarti, Lely (JPAS (Journal of Public Administration Studies), 2020)
This study aims to analyze public policy instruments chosen in the implementation of prostitution prevention and repetition policies in the city of Surabaya. This type of research is a qualitative descriptive study with a focus of research analyzing Voluntary Model Instruments, Mixed Model Instruments and Mandatory Instruments (Regulations). Novelty (novelty) of this research is to see the reality of the problem of prostitution by looking at the public policy instruments chosen in the implementation of prostitution prevention and repetition policies. The results showed that from the voluntary model instrument, commercial sex workers (CSWs) had been given skills training as well as spiritual spray/ recitation on a regular basis to then be repatriated to their home areas with compensation. However, not all sex workers want compensation. Residents of Dolly and Jarak held a bulletin board after hundreds of residents burned tires in the middle of the road as a refusal.